Resection of 2 Intradural Extramedullary Cervical Spine Tumors in a Patient With Neurofibromatosis Type 2: 3-Dimensional Operative Video. Issue 2 (5th June 2018) - Dekker, Simone E; Glenn, Chad A; Ostergard, Thomas A; Wu, Osmond C; Alonso, Fernando; Pace, Jonathan A; Rothstein, Brian D; Ray, Abhishek; Bambakidis, Nicholas C
Abstract: This 3-dimensional operative video illustrates resection of 2 cervical spine schwannomas in a 19-yr-old female with neurofibromatosis type 2. The patient presented with lower extremity hyperreflexity and hypertonicity. Magnetic resonance imaging (MRI) demonstrated 2 contrast-enhancing intradural extramedullary cervical spine lesions causing spinal cord compression at C4 and C5. The patient underwent a posterior cervical laminoplasty with a midline dural opening for tumor resection. Curvilinear spine cord compression is demonstrated in the operative video. After meticulous dissection, the tumors were resected without complication. The dural closure was performed in watertight fashion followed by laminoplasty using osteoplastic titanium miniplates and screws. Postoperative MRI demonstrated gross total resection with excellent decompression of the spinal cord. The postoperative course was uneventful. The natural history of this disease, treatment options, and potential complications are discussed.